Microbial Diversity in Sediments from the Bottom of the Challenger Deep, the Mariana Trench - Morono, Yuki; Nunoura, Takuro; Nishizawa, Manabu; Hirai, Miho; Shimamura, Shigeru; Inagaki, Fumio; Takai, Ken; Harnvoravongchai, Phurt; Miyazaki, Junichi; Takaki, Yoshihiro; Koide, Osamu; Fukui, Toshiaki (Microbes and Environments, 2018)
The Challenger Deep is the deepest ocean on Earth. The present study investigated microbial community structures and geochemical cycles associated with the trench bottom sediments of the Challenger Deep, the Mariana Trench. The SSU rRNA gene communities found in trench bottom sediments were dominated by the bacteria Chloroflexi (SAR202 and other lineages), Bacteroidetes, Planctomycetes, “Ca. Marinimicrobia” (SAR406), and Gemmatimonadetes and by the archaeal α subgroup of MGI Thaumarchaeota and “Ca. Woesearchaeota” (Deep-sea Hydrothermal Vent Euryarchaeotic Group 6). The SSU rRNA gene sequencing analysis indicated that the dominant populations of the thaumarchaeal α group in hadal water and sediments were similar to each other at the species or genus level. In addition, the co-occurrence of nitrification and denitrification was revealed by the combination of pore water geochemical analyses and quantitative PCR for nitrifiers.